(untitled) (Al-Academy, 2016)
The working of the some designer was recognize by the Production and introduction of the design which have special stemp and style determind by the experience and the Knowledge ability for the Designer which change the ordinaries shape to the develops shaps bening ideas and new meanings un known to the viewen make the design at high level of creative and the designer acquest experiennce and new skill in his way for the designs and the art march-out which clearly demonstrate on all the graphical work so the high research conserned on the knowledge and detect about the methods constructing of the ability and expernence for the graphic designer become it is decisive worker in effective or net effective the designers work and any consist which has renderingintel .Wher by the research consist four chapters, the first chapter select the research problem, which come in this question: what is the experience and the knowledge ability which must found in the graphic design throuy his graphic designer its clearly appear the important of the research through its sharing in difintion of the knowledge experience from the graphic designer and the develope of the visions and the skill powers of the worker in the field of the graphic designer.With mark the goals of the research in identihy about the ability of the graphic designer and his knowledge and skill experience through his graphic designer and detection about the designer skill and glamor ability and the innovation through the graphic design and the terminology found in it as the researcher developed the locative border represent by anumber from the graphic designer worker which were known and famous ,and the researcher developed the time border between (1996-2013)and developed the thene border which represent in (knowledge experience and the skill of graphic designer while the second section chapter which consist the theoretical frame which interest in three researcher ,the first research turning to(knowledge experience to the graphic designer while the the second research interest in (the experience and the skill ability of the graphic designer and the third research turning into about the(graphic designer and his specification )And emerge from the theoretical frame indicators as ascientific material helped the researcher in his measures and his way for research in analysis for consistency of four samples which searched in the third chapter which called (measures chapter )based on the analysis from which made by the researcher which taken from the theoretical frame the indicators ,and extracted it after showing it to the experience for evaluation and make sure from it is believable and fixed of important resulte help the research, while the fourth chapter consist of the showing of the resulte which resulte by resercher and the analysis resulte, the recommendations and suggestions